Reliability and Accuracy of Indoor Warehouse Navigation Using Augmented Reality - Petr Horejsi; Tomas Machac; Michal Simon (IEEE Access, 2024)
Augmented reality (AR) plays a crucial role in Industry 4.0, serving as a foundational element in various stages of the product and process lifecycle. AR is employed in both outdoor and indoor environments, utilising technologies such as GPS, SLAM, RFID, Wi-Fi, and inertial sensors for positioning and navigation. This study focuses on assessing the reliability, functionality, and accuracy of indoor warehouse navigation using inertial sensors commonly found in smartphones. Standard AR development tools like ARCore, AR Foundation, and ZXing were chosen for validation. A mobile application was developed using Unity3D. The field research was conducted in a medium-sized warehouse. Results showed an 83% success rate in reaching the target with an average accuracy of 0.48 metres. Development iterations addressed issues identified during testing including navigation failures and instability caused by warehouse lighting conditions. Comparisons with other technologies revealed AR’s competitive advantages, despite some existing challenges. The study concludes that ongoing innovation in hardware and software will likely overcome current limitations, paving the way for broader AR adoption in industrial settings.